Indigenous adolescent development - Whitbeck, Les B., author.
1 online resource (xviii, 282 pages)
Keywords: "This volume explores the first four waves of a longitudinal diagnostic study of Indigenous adolescents and their families. The first study of its kind, it calls attention to culturally specific risk factors that affect Indigenous (American Indian and Canadian First Nations) adolescent development and describe the historical and social contexts in which Indigenous adolescents come of age. It provides unique information on ethical research and development within Indigenous communities, psychiatric diagnosis at early and mid-adolescence, and suggestions for putting the findings into action through empirically-based interventions. "--